The Effect of Leaf Stacking on Leaf Reflectance and Vegetation Indices Measured by Contact Probe during the Season - Neuwirthová, Eva; Lhotáková, Zuzana; Albrechtová, Jana (Sensors (Basel, Switzerland), 2017)
The aims of the study were: (i) to compare leaf reflectance in visible (VIS) (400-700 nm), near-infrared (NIR) (740-1140 nm) and short-wave infrared (SWIR) (2000-2400 nm) spectral ranges measured monthly by a contact probe on a single leaf and a stack of five leaves (measurement setup (MS)) of two broadleaved tree species during the vegetative season; and (ii) to test if and how selected vegetation indices differ under these two MS. In VIS, the pigment-related spectral region, the effect of MS on reflectance was negligible. The major influence of MS on reflectance was detected in NIR (up to 25%), the structure-related spectral range; and weaker effect in SWIR, the water-related spectral range. Vegetation indices involving VIS wavelengths were independent of MS while indices combining wavelengths from both VIS and NIR were MS-affected throughout the season. The effect of leaf stacking contributed to weakening the correlation between the leaf chlorophyll content and selected vegetation indices due to a higher leaf mass per area of the leaf sample. The majority of MS-affected indices were better correlated with chlorophyll content in both species in comparison with MS-unaffected indices. Therefore, in terms of monitoring leaf chlorophyll content using the contact probe reflectance measurement, these MS-affected indices should be used with caution, as discussed in the paper. If the vegetation indices are used for assessment of plant physiological status in various times of the vegetative season, then it is essential to take into consideration their possible changes induced by the particular contact probe measurement setup regarding the leaf stacking.
Keywords: Seasons; chlorofyl; leaf optical properties; stromy; spectroradiometer; voda; seasonal dynamics; Plant Leaves; planar leaf; Water; Trees; leaf traits; SWIR; Salix caprea; broadleaved trees; Chlorophyll; spectral ranges; Populus tremula; VIS-NIR spectroscopy; roční období; listy rostlin